'Just How Things Are … ': Traumatic Lives in Natasha Kermani's Lucky. Issue 111 (2nd January 2022) - Sandes, Jasmine
ABSTRACT: This article discusses cinematic engagement with cyclical gendered violence and a present saturated in crisis in the film Lucky . As part of the broader cultural conversation about gendered violence and the #MeToo movement, this film presents an image of life after trauma and the dissonance between neoliberal feminisms that champion 'self-empowerment', and the ongoing crisis-state of traumatic aftermath. I argue that Lucky depicts the failures of postfeminist sensibilities to address systemic gendered violence, and the continued exclusion of women of colour from movements like #MeToo. Lucky staunchly resists demands for closure over trauma. This article explores the film's lack of resolution and perpetual sense of confusion as literalising the idea of living through a contemporary moment saturated in crisis. I argue that the film demonstrates both institutional and interpersonal failures to adequately respond to gendered violence, gesturing towards the need for support networks between victim-survivors.